Индивидуальная трудовая деятельность: вопросы и ответы : [справочное пособие / Савченко П. В. и др.] - Савченко Поль Вячеславович (Экономика, 1989)
Экземпляры: КХ (20100901) / Инвентарный номер: 951275 / Цена: 0.50 / Сис.шифр: 65.9(2)25 / Авт.знак: И 60 / ГРНТИ: 06.81 / ББК: 65.292.31